2010
DOI: 10.1063/1.3520666
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Al2O3-doped ZrO2 high-k dielectrics in three-dimensional stacked metal-insulator-metal capacitors

Abstract: In this paper, we report reliability evaluation results for nanomixed amorphous ZrAlxOy and symmetrically or asymmetrically stacked ZrO2/Al2O3/ZrO2 dielectric thin films grown by atomic layer deposition method in cylindrical metal-insulator-metal capacitor structure. Clear distinctions between their I-V asymmetry and breakdown behavior were correlated with the differences in compositional modification of bottom interface, defect density, and conduction mechanism of the film stacks. The thermochemical molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Each value shown is derived from the mean value of all capacitive areas of one substrate. The capacitance densities of the Al 2 O 3 based devices are similar to those reported by Chen et al 8 At fixed layer thicknesses, the capacitance density increases, when a so called high-k dielectric is added, where high-k means high permittivity. The high-k dielectrics used in this contribution are ZrO 2 and TiO 2 , which are integrated in a layered order in the nanolaminate, as described above.…”
mentioning
confidence: 49%
“…Each value shown is derived from the mean value of all capacitive areas of one substrate. The capacitance densities of the Al 2 O 3 based devices are similar to those reported by Chen et al 8 At fixed layer thicknesses, the capacitance density increases, when a so called high-k dielectric is added, where high-k means high permittivity. The high-k dielectrics used in this contribution are ZrO 2 and TiO 2 , which are integrated in a layered order in the nanolaminate, as described above.…”
mentioning
confidence: 49%
“…Reliability study for Al 2 O 3 -doped ZrO 2 thin films has confirmed such a relationship. 12 The capacitance-electric field (C-E) characteristics measured at different temperatures are presented in Fig. 2.…”
Section: B)mentioning
confidence: 99%
“…We notice a gradual increase in g with time until CC SET is reached and this is related to continuous trapping of positive charge [9] in the bulk and/or interfaces of Al 2 O 3 (enabled by a PF model with a given Φ level; see Figure 5(b)). It is thought that a high density of trapped positive charge would be able to modify the energy barriers of Al 2 O 3 during tunneling of carriers [9][10][11][12] (see Figure 5(c)), so that g conduction enhances while progressively reducing SET . For dissolution of the conductive filament, large CC RESET = 100 mA is required (producing Joule heating) and this produces a sudden decrease in gate current g which, in this case, is obtained after the first seconds of stressing bias.…”
Section: Resultsmentioning
confidence: 99%